Robust adaptive fuzzy filters output feedback control of strict-feedback nonlinear systems - Tong, Shaocheng; Liu, Changliang; Li, Yongming (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, an adaptive fuzzy robust output feedback control approach is proposed for a class of single input single output (SISO) strict-feedback nonlinear systems without measurements of states. The nonlinear systems addressed in this paper are assumed to possess unstructured uncertainties, unmodeled dynamics and dynamic disturbances, where the unstructured uncertainties are not linearly parameterized, and no prior knowledge of their bounds is available. In recursive design, fuzzy logic systems are used to approximate unstructured uncertainties, and K-filters are designed to estimate unmeasured states.
Keywords: nonlinear systems; adaptive fuzzy control; backstepping; small-gain approach; K-filters